50 ways to protect your identity and your credit : everything you need to know about identity theft, credit cards, credit repair, and credit reports - Weisman, Steve (Pearson/Prentice Hall, 2005)
Everything You Need to Know About Identity Theft, Credit Cards, Credit Repair, and Credit Reports "The author substitutes straight talk for legal mumbo-jumbo in 50 Ways to Protect Your Identity and Your Credit. Reading this book is like getting a black belt in consumer self-defense."--Jim Bohannon, host of The Jim Bohannon Show "Identity theft is among the fastest-growing problems facing Americans today. This book will help you learn all you need to know to protect your lives, money, and security. Consider it your first stop in your quest for knowledge and guidance to prevent ID theft." -Robert Powell, Editor of CBS MarketWatch "As one who has lived through some of the nightmare scenarios discussed by the author, I believe "Steve's Rules" (Chapter 14) need to be placed in a prominent place so you can see them any time you think you are safe. They may be the new practical commandments for financial survival." -Doug Stephan, host of the Good Day nationally syndicated radio show "Detecting and stopping identity thieves is imperative to protecting your finances and financial reputation. Steve Weisman shows you how to protect yourself and what steps to take if you are victimized. This is a must-read for anyone with a bank account and a credit card!" -Bonnie Bleidt, Boston Stock Exchange Reporter, CBS4 Boston, Host of Early Exchange, WBIX Don't be a victim! Save your identity, save your credit-and save a fortune! 10,000,000 Americans had their identities stolen last year-don't be the next! Discover easy steps you can take now to reduce your vulnerability. Recognize "phishing" and other identity scams-online and off. Learn what you must do immediately if you've been attacked. Defend yourself against credit rip-offs, and stop paying more than you have to! It's all here: simple rules, handy checklists, even easy-to-use form letters! © Copyright Pearson Education. All rights reserved